Type XVII Collagen is a Key Player in Tooth Enamel Formation - Asaka, Takuya (American Society for Investigative Pathology, 2009)
Inherited tooth enamel hypoplasia occurs due to mutations in genes that encode major enamel components. Enamel hypoplasia also has been reported in junctional epidermolysis bullosa, caused by mutations in the genes that encode type XVII collagen (COL17), a component of the epithelial-mesenchymal junction. To elucidate the pathological mechanisms of the enamel hypoplasia that arise from the deficiency of epithelial-mesenchymal junction molecules, such as COL17, we investigated tooth formation in our recently established Col17(−/−) and Col17 rescued mice. Compared with wild-type mice, the incisors of the Col17(−/−) mice exhibited reduced yellow pigmentation, diminished iron deposition, delayed calcification, and markedly irregular enamel prisms, indicating the presence of enamel hypoplasia. The molars of the Col17(−/−) mice demonstrated advanced occlusal wear. These abnormalities were corrected in the Col17 rescued humanized mice. Thus, the Col17(−/−) mice clearly reproduced the enamel hypoplasia in human patients with junctional epidermolysis bullosa. We were able to investigate tooth formation in the Col17(−/−) mice because the Col17(−/−) genotype is not lethal. Col17(−/−) mouse incisors had poorly differentiated ameloblasts that lacked enamel protein-secreting Tomes’ processes and reduced mRNA expression of amelogenin, ameloblastin, and of other enamel genes. These findings indicated that COL17 regulates ameloblast differentiation and is essential for normal formation of Tomes’ processes. In conclusion, COL17 deficiency disrupts the epithelial-mesenchymal interactions, leading to both defective ameloblast differentiation and enamel malformation.